2011
DOI: 10.1016/j.electacta.2011.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Modification of nanoelectrode ensembles by thiols and disulfides to prevent non specific adsorption of proteins

Abstract: a b s t r a c tThe possibility to functionalize selectively with thiols or disulfides the surface of the gold nanoelectrodes of polycarbonate templated nanoelectrode ensembles (NEEs) is studied. It is shown that the Au nanoelectrodes can be coated by a self assembled monolayer (SAM) of thioctic acid (TA) or 2-mercaptoethanesulfonic (MES) acid. The study of the electrochemical behavior of SAM-modified NEEs by cyclic voltammetry (CV) at different solution pH, using ferrocenecarboxylate as an anionic redox probe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…Therefore, the AFM scans were performed on a relatively large spatial scale, examining areas 50 50 mm wide. At variance with the previous paper [37], working with such a wide spatial scale, the single nanoelectrodes are only scarcely distinguished from the surrounding polycarbonate. Relevant AFM topographies are shown in Figure 3, where Figure 3A refers to a brand new NEE and Figure 3B shows the topography of a NEE after being used in 1 M HCl.…”
Section: Selection Of the Electrolytementioning
confidence: 83%
See 3 more Smart Citations
“…Therefore, the AFM scans were performed on a relatively large spatial scale, examining areas 50 50 mm wide. At variance with the previous paper [37], working with such a wide spatial scale, the single nanoelectrodes are only scarcely distinguished from the surrounding polycarbonate. Relevant AFM topographies are shown in Figure 3, where Figure 3A refers to a brand new NEE and Figure 3B shows the topography of a NEE after being used in 1 M HCl.…”
Section: Selection Of the Electrolytementioning
confidence: 83%
“…It was recently shown that AFM can furnish useful information on the morphology of NEEs [37]. Note that, in the present case, we are interested more in the general behavior of all the assembly rather than on the destiny of the individual nanoelectrodes.…”
Section: Selection Of the Electrolytementioning
confidence: 99%
See 2 more Smart Citations
“…Growth of the nanoelectrodes in track-etched polycarbonate membranes was performed according to the electroless procedure proposed by Menon and Martin [1] and following modifications [15].…”
Section: Fabrication Of Nees and Modification With Aunpsmentioning
confidence: 99%